2022
DOI: 10.1177/15579883221078145
|View full text |Cite
|
Sign up to set email alerts
|

Social Disconnection and Psychological Distress in Canadian Men During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has significantly challenged many men’s mental health. Efforts to control the spread of the virus have led to increasing social disconnection, fueling concerns about its long-term effects on men’s mental health, and more specifically their experience of psychological distress. Social disconnection, psychological distress, and the relationship between them have yet to be formally explored in a Canadian male sample during the COVID-19 pandemic. The present study examined whether reduced soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Individuals who reported COVID-19 symptoms were mandated to be quarantined and if tested positive for COVID-19, they had to be isolated to prevent further spread of the disease [ 25 ]. This resulted in social isolation that exacerbated fears, anxieties, and depression [ 25 27 ]. Such actions of social isolation could explain why those who reported COVID-19 symptoms were more likely to experience psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who reported COVID-19 symptoms were mandated to be quarantined and if tested positive for COVID-19, they had to be isolated to prevent further spread of the disease [ 25 ]. This resulted in social isolation that exacerbated fears, anxieties, and depression [ 25 27 ]. Such actions of social isolation could explain why those who reported COVID-19 symptoms were more likely to experience psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the positive strategies, a number of studies showed that preservation of social ties, even if virtual, made men less prone to presenting depression and anxiety symptoms, reinforcing the need for interventions aimed at promoting health literacy, connectivity, and social support for men to help minimize some psychosocial problems, such as impacts induced by COVID-19 ( Moreira et al, 2021 ; Moura et al, 2022 ; Nguyen et al, 2020 ; Paakkari & Okan, 2020 ; Sentell et al, 2020 ; Simpson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, we observed an increasing number of international studies focused only on epidemiological aspects related to men’s mental health ( Adamyan et al, 2022 ; Ahrenfeldt et al, 2021 ; Al-Sejari & Al-Kandari, 2022 ; Kamalov et al., 2021 ; Simpson et al, 2022 ). In addition, to the present day, few studies have been published that explore the need to understand the dynamics of the experiences presented in pandemic contexts and their relationship with human health ( Wilson et al, 2022 ), with a considerable gap in scientific evidence in Latin American countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted December 13, 2022. ; https://doi.org/10.1101/2022.12.12.22283388 doi: medRxiv preprint stressors (120,121), such as done by COVID-19 pandemic, the mind is bound to be impacted if no interventions are put in place (8,117,(122)(123)(124)(125).…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%